Sequential Exploratory Organization Analysis Citizenship Behavior, Paud Teacher In Cirebon City - Sastrawijaya, Ade; Retnowati, Rita; Hardhienata, Soewarto; Zainal Arifin, M. (Opción, 2019)
Organization Citizenship Behavior (OCB) Early Childhood Education Teach- ers (PAUD) become a very important part in the development of education, especially in facing demographic bonuses in Indonesia. This study aims to find variables related to OCB, the relationship model and the value of the strength of these variables with OCB. This research uses Mixed Sequential Explora- tory Method. Data were collected from 196 PAUD teachers in Cirebon City. The quantitative research data were then analyzed using the SITOREM (Sci- entific Identification Theory to Conduct Research in Education Management) method to set recommendations and determine the order of priority in han- dling indicators that must be improved. The results of qualitative research found three variables related to OCB, namely organizational support varia- bles, serving leadership, and work involvement. The results of quantitative re- search are (1) there is a positive relationship between organizational support and OCB (ryx1 = 0.492), (2) there is a positive relationship between leadership serving with OCB (ryx2 = 0.503), (3) there is a positive relationship between work engagement with OCB ( ryx3 = 0.520). Based on the SITOREM analysis that the priority variables that must be corrected are work involvement with indicators (1) the importance of individual good work, (2) clarity of work, (3) work involvement because of being attracted/called by the objectives to be achieved, (4) development opportunities self.